2011
DOI: 10.1029/2010jd015563
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and diurnal variations of black carbon and organic carbon aerosols in Bangkok

Abstract: [1] Measurements of black carbon (BC) and organic carbon (OC) were conducted in Bangkok during [2007][2008]. Annual trends of BC and OC show strong seasonality with lower and higher concentrations during wet and dry seasons, respectively. Flow of cleaner air, wet removal, and negligible biomass burning resulted in the lowest concentrations of aerosols in the wet season. In addition to anthropogenic sources, long-range transport and biomass burning caused higher concentrations in the dry and hot seasons, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 70 publications
4
47
2
1
Order By: Relevance
“…The semi-enclosed Bohai Sea and Yellow Sea, from the moderatehigh latitude region, are mainly situated at the downwind area of the East Asian Monsoon, receiving large amounts of combustionderived substances (e.g., PAHs) through atmospheric deposition, especially in the winter season due to the extensive regional heating activities in China (Wang et al, 2014). The surrounding region of the GOT from the tropical regime is more subjected to the extensive biomass burning, especially during the hot season (Sahu et al, 2011). Although there is no extensive coal consumption around the GOT, such as that in North China, the inherent biomass burning in tropical SE Asia is also significant (Bond et al, 2004), and atmospheric deposition is expected to be an important BC vector for the Indian Ocean (Lohmann et al, 2009).…”
Section: Mass Inventory Of Bc In the Got Sediments And Its Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…The semi-enclosed Bohai Sea and Yellow Sea, from the moderatehigh latitude region, are mainly situated at the downwind area of the East Asian Monsoon, receiving large amounts of combustionderived substances (e.g., PAHs) through atmospheric deposition, especially in the winter season due to the extensive regional heating activities in China (Wang et al, 2014). The surrounding region of the GOT from the tropical regime is more subjected to the extensive biomass burning, especially during the hot season (Sahu et al, 2011). Although there is no extensive coal consumption around the GOT, such as that in North China, the inherent biomass burning in tropical SE Asia is also significant (Bond et al, 2004), and atmospheric deposition is expected to be an important BC vector for the Indian Ocean (Lohmann et al, 2009).…”
Section: Mass Inventory Of Bc In the Got Sediments And Its Comparisonmentioning
confidence: 99%
“…6), which could be partially explained by a decoupling of the char and soot sources as noted above. Biomass burning and forest fires have been suggested to serve as the predominant sources for BC in aerosol samples in Thailand, especially in the hot season (Sahu et al, 2011), and the larger particles of char mainly from the biomass burning residues tend to first accumulate in soils in close proximity to their site of production and then be primarily transported by surface run-off and local river inputs to the aquatic sediments (Gelinas et al, 2001;Yunker et al, 2002;Pietzsch et al, 2010;Han et al, 2015a). Actually, in addition to the sedimentassociated BC, Ding et al (2015) also demonstrated that there existed different input sources for the dissolved BC in the boreal forest streams through active removal process in soils from the local biomass burning as compared to those in the remote glacial rivers with a more atmospheric delivered fossil fuel-derived BC.…”
Section: Occurrence and Input Pathways Of Char And Soot In The Gotmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have focused on the chemical composition of aerosols and their impact on the tropical/sub-tropical urban environment over the past two decades (Fang et al, 1999;Latha and Badarinath, 2003;2005;Pandey et al, 2006) while others have examined the empirical estimation of secondary organic carbon (SOC) formation (Seguel et al, 2009;Grivas et al, 2012;Kim et al, 2012;Wang et al, 2012). Only a few publications have presented indepth, quantitative evidence regarding the behavior of carbonaceous aerosols in Thailand (Pongpiachan et al, 2009;Sahu et al, 2011;Li et al, 2012).…”
Section: Ilpe Ilpe)mentioning
confidence: 99%
“…Two observatory stations, namely Baiyoke Suit Hotel (13°45'10.65" N 100°32'24.92" E) : There have, however, been an increasing number of articles to appear in several peer-reviewed international journals over the past few years, which relate to of haze episodes on the air quality in the northern region of Thailand (Kim et al, 2011;Wiwatanadate and Liwsrisakun, 2011;Li et al, 2012). For instance, one study observed a 20% rise in the number of patients suffering from respiratory diseases in March 2007 when compared to one year earlier in 2006 (Pengchai et al, 2009 : In 1971, The Environmental Protection Agency (EPA) promulgated primary and secondary national ambient air quality standards for particulate matter measured as "total suspended particulate" or "TSP".…”
Section: Ilpe Ilpe)mentioning
confidence: 99%